Role of Parental Involvement in Enhancing Early Childhood Education Outcomes in Japan - Taniguchi, Mika (Journal of Education and Practice, 2026)
Purpose: The purpose of this article was to analyze role of parental involvement in enhancing early childhood education outcomes. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research on the effect of teacher professional development (PD) on student academic performance in mathematics in the United States consistently shows moderate to positive improvements in student outcomes when teachers engage in well-structured and sustained PD programs. Studies indicate that PD programs designed to enhance teachers' instructional strategies and content knowledge, particularly in mathematics, are linked to measurable gains in student achievement, with moderate effect sizes found on test scores. Moreover, research suggests that ongoing, collaborative, and long-duration PD, such as coaching or embedded professional learning communities, tends to have a more significant impact on student learning than short-term workshops or one-off seminars. Unique Contribution to Theory, Practice and Policy: Ecological systems theory, social capital theory & family systems theory may be used to anchor future studies on the role of parental involvement in enhancing early childhood education outcomes. Practitioners should develop interactive, hands-on training for parents on how to engage in their child’s academic development at home, with a focus on improving literacy, numeracy, and social skills. At the policy level, education policymakers should prioritize the creation of national and local policies that support parental involvement as a core component of early childhood education.